Working in the Vineyard of the Lord : Jesuit Confraternities in Early Modern Italy. - Lazar, Lance (University of Toronto Press, 2014)
Working in the Vineyard of the Lord represents the first assessment of an entire confraternal network affiliated with a single religious order in the Early Modern period.